Employing cultural forms in the works of Mohammed Ghani Hikmat and Murtada Haddad (Al-Academy, 2018)
Man always reacts by employing data that he lives inside Artworks and he tries to make them an ideal speech that shows the most important intellectual trends to which he belongs, as it happened in the formal building of the ancient arts . Mesopotamia is one of the civilizations that interacted with the intellectual legibility transforming into visual symbols, so it is difficult for the researcher to interpret these symbols without considering the nature of these civilizations in general .This current search aims to identify similarities and differences in the recruitment of cultural shapes between the works of the sculptors (Mohammed Ghani Hikmat and Murtada Haddad) .Researcher adopted an approach of analytical description of the sample of his research employing cultural forms in the Iraqi contemporary sculpture, where the selected pieces of his research represent sculptures in Iraq completed within the time limits of research between the years (1970-1990). And here, the researcher analyzed two types of works of (Mohammed Ghani Hikmat and Murtada Haddad) and he has got a set of important results such as :-1-The nature of employing the cultural forms in the sculptural works was beyond the discourse of the modern and contemporary sculpture or in its academic or classical style that sculptor had overriding them to another style by summoned an Iraqi technician achieved fully as in the model (1,4) .2-Note the emergence deductible portion of the Sumerian statues, linked with artist completed sculptured and he employed it to connect many important rhetorical sentences as in the model (1,3)